Formulation of functional instant pumpkin cream soup with moringa leaves as nutritional support for breastfeeding mothers - Atikah Fajriani; Sri Anna Marliyati; Budi Setiawan (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
The exclusive breastfeeding rate has declined, partly due to mothers' perceptions of inadequate breast milk production. Optimal nutrition is crucial to enhance breast milk production. This study aimed to develop instant pumpkin cream soup with moringa leaves, which contains beta-carotene, flavonoids, and phenols as galactagogues and supports meeting the nutritional needs of breastfeeding mothers. Conducted from January to April 2024 in Bogor, West Java, the study used a Randomized Design (CRD) with moringa leaf concentrations of 1%, 2%, and 3%. A sensory evaluation by 35 semi-trained panelists indicated that the highest moringa concentration (F3) achieved the best taste, consistency, and overall acceptability scores. Statistical analysis revealed significant differences in moisture and protein contents between fresh and instant cream soups (p<0,05). The selected formula contained 0,22 mg/g iron, antioxidant activity (IC50:167,79 ppm), 50,95 mg GAE/g total phenols, 20,33 mg QE/g total flavonoids, and 40,50 mcg/g beta-carotene, with a protein digestibility of 43,57%. One serving (25 g) of cream soup provided 5% of the Recommended Dietary Allowance (RDA) for breastfeeding mothers. In conclusion, cream soup formula with 3% moringa leaves was the most preferred, containing nutrients and antioxidants that support increased breast milk production and meet the nutritional needs of breastfeeding mothers.